2015
DOI: 10.1016/j.ijchp.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Parental and individual predictors of trajectories of depressive symptoms in Chilean adolescents

Abstract: Depressive symptoms are prevalent in adolescence, but not all adolescents experience the same level or evolution of symptoms, suggesting the need to identify differences in trajectories of symptoms. We used Growth Mixture Modeling to analyze different trajectories of depressive symptoms in a sample of 1,072 Chilean adolescents (12-15 years old, 54% female). First, a baseline model was selected and then adolescent irritability, maternal warmth, demandingness and disrespect were introduced to the model as predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Scholars using these approaches have assessed depressive symptoms in various ways, ranging from brief self‐reports (e.g., Chaiton et al, ; Costello, Swendsen, Rose, & Dierker, ; Cumsille, Martínez, Rodríguez, & Darling, ; Repetto, Caldwell, & Zimmerman, ) to extensive, clinically oriented questionnaires and structured interviews (e.g., Briere, Janosz, Fallu, & Morizot, ; Duchesne & Ratelle, ; Ellis et al, ; Mezulis, Salk, Hyde, Priess‐Groben, & Simonson, ; Reinke, Eddy, Dishion, & Reid, ; Wickrama & Wickrama, ; Wu, ; Yaroslavsky, Pettit, Lewinsohn, Seeley, & Roberts, ). In addition, some studies have focused on the development of depressive symptoms across the entire span of adolescence (Chaiton et al, ; Costello et al, ; Dekker et al, ; Diamantopoulou, Verhulst, & van der Ende, ; Ellis et al, ; Ferro, Gorter, & Boyle, ; Mezulis et al, ; Wickrama & Wickrama, ; Yaroslavsky et al, ), whereas others have been limited to either early (Brendgen, Wanner, Morin, & Vitaro, ; Briere et al, ; Cumsille et al, ; Duchesne & Ratelle, ; Reinke et al, ; Sallinen, Rönkä, Kinnunen, & Kokko, ) or late (Rodriguez, Moss, & Audrain‐McGovern, ; Stoolmiller, Kim, & Capaldi, ) adolescence.…”
Section: Depression Among North American Indigenous Groupsmentioning
confidence: 99%
“…Scholars using these approaches have assessed depressive symptoms in various ways, ranging from brief self‐reports (e.g., Chaiton et al, ; Costello, Swendsen, Rose, & Dierker, ; Cumsille, Martínez, Rodríguez, & Darling, ; Repetto, Caldwell, & Zimmerman, ) to extensive, clinically oriented questionnaires and structured interviews (e.g., Briere, Janosz, Fallu, & Morizot, ; Duchesne & Ratelle, ; Ellis et al, ; Mezulis, Salk, Hyde, Priess‐Groben, & Simonson, ; Reinke, Eddy, Dishion, & Reid, ; Wickrama & Wickrama, ; Wu, ; Yaroslavsky, Pettit, Lewinsohn, Seeley, & Roberts, ). In addition, some studies have focused on the development of depressive symptoms across the entire span of adolescence (Chaiton et al, ; Costello et al, ; Dekker et al, ; Diamantopoulou, Verhulst, & van der Ende, ; Ellis et al, ; Ferro, Gorter, & Boyle, ; Mezulis et al, ; Wickrama & Wickrama, ; Yaroslavsky et al, ), whereas others have been limited to either early (Brendgen, Wanner, Morin, & Vitaro, ; Briere et al, ; Cumsille et al, ; Duchesne & Ratelle, ; Reinke et al, ; Sallinen, Rönkä, Kinnunen, & Kokko, ) or late (Rodriguez, Moss, & Audrain‐McGovern, ; Stoolmiller, Kim, & Capaldi, ) adolescence.…”
Section: Depression Among North American Indigenous Groupsmentioning
confidence: 99%
“…Most studies have found that four latent trajectories best characterize the data; however, differences exist, with some studies finding as few as three and others as many as six (Ellis et al, 2017). Most of these studies focus on adolescents only (Brendgen, Wanner, Morin, & Vitaro, 2005; Fernandez Castelao & Kröner-Herwig, 2012; Rodriguez, Moss, & Audrain-McGovern, 2005; Sallinen, Rönkä, Kinnunen, & Kokko, 2007) or utilized samples that are either nonrandom (Chaiton et al, 2013, Repetto, Caldwell, & Zimmerman, 2005), unrepresentative of U.S. populations (Brendgen et al, 2005; Cumsille et al, 2015; Dekker et al, 2007), or both (Chaiton et al, 2013; Repetto et al, 2005).…”
Section: Trajectories Of Adolescent Depressionmentioning
confidence: 99%
“…However, Cumsille et al claimed that depressive symptoms that develop in adolescence have a considerable impact on health in adulthood. 4 It is, therefore, necessary to delve into the characteristics of childhood depression and, in addition to determining the prevalence of children with serious depressive symptomatology, discover how many have less severe symptoms. Normally, the studies show data with more severe symptoms of childhood depression, but the percentages of children who have risk symptoms are barely identified, and if such symptoms are not detected and eliminated early on, they could turn into severe cases of depression in the not-too-distant future.…”
Section: Introductionmentioning
confidence: 99%